Spatiotemporal variability of soil salinity and the driving factors of cultivated land in Xinjiang, China - Zhang, Yue; Ye, Huichun; Liu, Ronghao; Nie, Chaojia; Tang, Mingyao; Huang, Yuanfang; Wang, Hongye; Zhao, Xiaoshu; Wang, Weini; Lyu, Zhijun (International Journal of Agricultural and Biological Engineering, 2025)
Soil salinization poses a major challenge to agricultural production, food security, and sustainability in arid and semi-arid regions worldwide. Effectively addressing this issue requires a thorough understanding of the spatiotemporal variations in soil salinity and its driving factors. This study investigates soil salinity in Xinjiang, China, using geostatistical methods to analyze its spatial distribution in cultivated lands across the region and its southern and northern sub-regions in 2021. Additionally, it examines the spatiotemporal changes in soil salinity from 2011 to 2021 in Bachu County (southern Xinjiang) and Nileke County (northern Xinjiang), which serve as representative areas. The results showed that in 2021, soil salinity across Xinjiang ranged from 0.1 to 27.7 g/kg, with an average of 2.8 g/kg and a coefficient of variation of 130.4%, indicating significant variability. Soil salinity levels were higher in southern Xinjiang (3.8 g/kg) compared to northern Xinjiang (2.0 g/kg), showing a spatial trend of “increasing salinity from north to south.” Key drivers of spatial variation included available potassium, mean annual precipitation, alkali-hydrolyzable nitrogen, elevation, and soil pH. Between 2011 and 2021, soil salinity in cultivated lands increased significantly by 2.0 g/kg in Bachu County, while it decreased by 4.2 g/kg in Nileke County, with these changes mainly influenced by climatic factors such as precipitation, evapotranspiration, and surface temperature. These findings provide critical insights and data support for monitoring and managing soil salinization in Xinjiang, offering valuable guidance for improving agricultural sustainability in the region. Key words: soil salinization; spatial-temporal variation; driving factors; Xinjiang DOI: 10.25165/j.ijabe.20251802.9486 Citation: Zhang Y, Ye H C, Liu R H, Nie C J, Tang M Y, Huang Y F, et al. Spatiotemporal variability of soil salinity and the driving factors of cultivated land in Xinjiang, China. Int J Agric & Biol Eng, 2025; 18(2): 197–207.